Menanamkan Kesadaran Lingkungan Melalui Ecoprint Bersama Siswa-Siswi SDN Pondok Kecamatan Karanganom - sriyono, Fitri Alvina Suha; Nurcahyanti, Desy (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
The aim of this research is to explain how ecoprint results can be used as a means of expression in the arts and culture learning process. The aim of community service is ecoprint work created by Pondok Elementary School students. The ecological printing technique uses simple fabric dyes to produce unique and original motifs. The principle of ecoprinting is to attach colored pigments to certain fabric media, such as leaves, flowers, stems or other body parts. SDN Pondok uses the method of hitting leaves on the canvas using a wooden mallet. The fabric is dried directly in the sun. The research results show that the ecoprint technique should be used at SDN Pondok as a new tool in developing fine art works which usually only draw on drawing paper. The results of this service activity improve the skills of Pondok Karanganom District Elementary School students in instilling environmental awareness through ecoprint. Keywords: Eoprint, Personal Expression, Learning, Service, School.